Efficacy of non-surgical therapy on IL-6 levels in patients with chronic periodontitis: A systematic review - Winiati, Endang; Alwiyansyah, Annisa Nurrahma; Sebastian, James; Owen, Kevin; Anggun, Gheta (Dentika: Dental Journal, 2024)
Chronic periodontitis-affected tissues have an increased production of pro-inflammatory cytokines relative to anti-inflammatory counterparts, including IL-6. Therefore, this systematic review aimed to synthesize and appraise the available literature to provide a comprehensive analysis of the efficacy of non-surgical therapy, specifically focusing on the therapeutic effect of IL-6 in patients with chronic periodontitis. This review focused on seven studies including 308 patients with moderate to severe chronic periodontitis across five different countries. The RoB assessment showed a moderate to low risk of bias studies. Moreover, the studies found a statistically significant decrease in IL-6 levels in patients after receiving non-surgical therapy. There were statistically significant alterations in periodontal indices and IL-6 levels over time, which showed the efficacy of non-surgical treatment based on various literature. Hence, decreasing IL-6 could serve as a therapeutic indicator of inflammatory response.